Pengaruh Kompensasi Intrinsik Dan Kompensasi Ekstrinsik Serta Pelatihan Kerja Kerja Terhadap Kinerja Karyawan - Riandiyani, Mirza; Sriathi, Anak Agung Ayu (E-Jurnal Manajemen, 2013)
This research done with purpose to know variable compensation intrinsic and compensation extrinsic and training work effect on employee performance simultaneously and partial, and free variables are the dominant the performance on employee at the gangsa private villa sanur. Analysis of technique used was multiple linear regression analysis and used to test the hypothesis simultaneously, partial and standardized coefficients beta . The result analysis shows that simultaneously and partial variable compensation intrinsic, and compensation extrinsic and training work influential positive and significantly to employee performance. Variable compensation extrinsic in research is a variable that has a dominant influence on the performance employee based on a calculation analysis standardized coefficients beta having the highest value. Keywords : Intrinsic compensation, extrinsic compensation,  job training, employee performance